Book Review: European States and Their Muslim Citizens: The Impact of Institutions on Perceptions and Boundaries - Harun, Minah (Universiti Utara Malaysia Press, 2014)
Editors: Bowen, J. R., Bertossi, C., Duyvendak, J. W., & Krook, M. L. (Eds.)(Cambridge: Cambridge University Press, 2014. 285 pp. ISBN 978-1-107-03864-6)